Teaching in Bad Times - Ohmann, Richard (Radical Teacher, 2022)
[…] it seems a little timid, if not dangerously evasive, for people in and around education not to be entertaining dire thoughts about the challenges it may face and its future, given the specters that haunt capitalism today. I do not hear such thoughts among progressives, beyond worry and anger about continuing trends: privatization of this public good; casualizing of labor; severe funding cuts as states and localities struggle with big deficits; the relentless march of high-stakes tests. . . .I do expect more from educational workers on the left -- more than our usual plans to raise consciousness in individual classrooms and fight rear guard actions against deteriorating conditions of labor.